Harga Diri, Konformitas dan Perilaku Seksual Remaja Dalam Berpacaran - Garvin Garvin (Jurnal Ilmu Perilaku, 2018)
Sexual behavior on dating in adolescents dating is increasingly apprehensive. Various data shows that adolescents in Jakarta have done sexual intercourse before marriage. The adolescents are willing to have sex with his/her girlfriend/boyfriend based on various reasons, such as forced by boyfriend/girlfriend, feel ready to do it, need to be loved, or afraid of being teased by friends (Santrock in Sarwono, 2013). The study intends to know the relationship between self-esteem and conformity with adolescents’ sexual behavior on dating. The study participants of 137 Jakarta adolescents who had been dating before (69.3% were female) were included in the study. Research participants were asked to fill the Rosenberg Self-Esteem Scale that has been adapted into Bahasa Indonesia, assertivity scale, and sexual behavior scale. All the three scales are filled online and anonymous to convince research participants to answer honestly. The results of this study indicate that there is no significant relationship between self-esteem and adolescent sexual behavior (p = 0.364> 0.05; rs = 0.078) and there is a significant relationship between conformity with adolescent sexual behavior in dating (p = 0.043 <0.05; rs = 0.173). This study confirms that conformity is one of the causes of negative behavior in adolescents.